Homens distintos : consumo, construção do corpo e identidade gay viril - Reis, Diego Nunes (2013)
The goal of this dissertation is to analyze consumption, body building and the identity of individuals who identify with a gay identity. To this end, we conducted an ethnographic research and sought input on the theoretical perspective taken by some authors as a reference in the themes addressed. We also carried out an analysis of some academic papers and journalistic in order to sustain the discussions held during the course of the chapters. The notion of "gaycidade" perceived as a social experience that is different from calling homosexuality was selected as an analytical category. As a reflection on the existence of gays circuits, consumption spaces and sociability that allowed the emergence of numerous representations in relation to gay identity, for example, here called manly or gay distinguished men.